Versatile MXenes for aqueous zinc batteries - Liu, Huan (2024)
Aqueous zinc-ion batteries (AZIBs) are gaining popularity for their cost-effectiveness, safety, and utilization of abundant resources. MXenes, which possess outstanding conductivity, controllable surface chemistry, and structural adaptability, are widely recognized as a highly versatile platform for AZIBs. MXenes offer a unique set of functions for AZIBs, yet their significance has not been systematically recognized and summarized. This review article provides an up-to-date overview of MXenes-based electrode materials for AZIBs, with a focus on the unique functions of MXenes in these materials. The discussion starts with MXenes and their derivatives on the cathode side, where they serve as a 2D conductive substrate, 3D framework, flexible support, and coating layer. MXenes can act as both the active material and a precursor to the active material in the cathode. On the anode side, the functions of MXenes include active material host, zinc metal surface protection, electrolyte additive, and separator modification. The review also highlights technical challenges and key hurdles that MXenes currently face in AZIBs.